2016
DOI: 10.1080/15513815.2016.1242675
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Adipokines in Cord Blood and at 72 h in Discordant Dichorionic Twins

Abstract: IUGR is related to lower leptin level and proatherogenic lipid profile (higher TG and lower HDL-C), which are not influenced by adipokine at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In addition, we found that in the second and third trimesters of pregnancy, fetal weight and AC were negatively associated with cord blood TG. This finding is consistent with previous studies which found that fetuses with intrauterine growth restriction had higher cord blood TG compared with normal-growth fetus ( 29 , 30 ). Another study showed that AC was negatively associated with cord blood TG levels among growth-restricted fetuses ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found that in the second and third trimesters of pregnancy, fetal weight and AC were negatively associated with cord blood TG. This finding is consistent with previous studies which found that fetuses with intrauterine growth restriction had higher cord blood TG compared with normal-growth fetus ( 29 , 30 ). Another study showed that AC was negatively associated with cord blood TG levels among growth-restricted fetuses ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…Statistical analyses were performed using Statistica version 13.1 (Statsoft, Poland). The sample size of 32 pair of twins (64 patients) has been shown to have a statistically significant impact on the assessment of insulin resistance and endocrine disorders both for the twin and singleton gestation population studies 23,24 . The distribution of the analyzed data was checked by Shapiro-Wilk test.…”
Section: Statistical Data Analysismentioning
confidence: 99%
“…Simultaneously, it was suggested that placental insufficiency is associated with an increase in placental leptin production . Furthermore, some studies demonstrated that leptin levels are lower in IUGR, but differences were not significant , and it was also reported that cord blood leptin levels did not differ significantly in IUGR compared to normal pregnancies . These data suggest that the association between leptin and IUGR is controversial.…”
Section: Leptin and Pathologies Associated With Pregnancymentioning
confidence: 99%